THE PROJECTION OF THE DEVELOPMENT OF FOLKS’ FARM AS THE CONCEPT OF AGRO-TOURISM AS AN EFFORT TO INCREASE ECONOMIC BENEFITS OF SMALL-SCALE LIVESTOCK BUSINESS - Halim Ahmad; Muhammad Musyafi’i Huda; Yunus Adi Julianto; Monita Januar (UPT Penerbitan Universitas Jember)
The most main cause of the failed folks’ livestock business in Indonesia in order to continue and survive is because they are generally still rely on the traditional techniques of breeding. It causes the productivity of livestock that would have an impact on the lower income for breeders. Therefore, it needs requirements that are more active efforts in order to maintain the existence of folks’ livestock by doing diversification. This research was carried out in Dangean, Boyolali Regency by using qualitative descriptive method. The data collecting are done by interview, which is conducted in accidental; with the number of respondents are 10 people. Ambarrukmo Tourism Institute (STIPRAM) researchers found that the techniques and equipment of dairy farmers activity in the Dangean’s folks’ who still traditional have attractiveness. The farming activity that integrated with the beauty of the visual landscape of the village, and it is supported by the comfortable and cool natural atmosphere of countryside at the mountain slope, and also the harmony of people which is still reflected in the economic and social activity give the strength for dairy farmers in Dangean to diversify their farm into agro-tourism.